2022
DOI: 10.1109/tro.2021.3128328
|View full text |Cite
|
Sign up to set email alerts
|

Approximating Displacements in ${\mathbb {R}}^3$ by Rotations in ${\mathbb {R}}^4$ and Its Application to Pointcloud Registration

Abstract: No proper norm exists to measure the distance between two object poses essentially because a general pose is defined by a rotation and a translation, and thus it involves magnitudes with different units. As a means to solve this dimensionalinhomogeneity problem, the concept of characteristic length has been put forward in the area of kinematics. The idea consists in scaling translations according to this characteristic length and then approximating the corresponding displacement defining the object pose in R 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recently, it has been found that some problems arising in robotics, computer vision, and computer graphics—such as point‐cloud registration 1 and hand‐eye calibration problems 2 —can be formulated in terms of 4D rotation matrices. Unfortunately, experimental data leads to noisy 4D rotation matrices whose orthonormality must be restored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that some problems arising in robotics, computer vision, and computer graphics—such as point‐cloud registration 1 and hand‐eye calibration problems 2 —can be formulated in terms of 4D rotation matrices. Unfortunately, experimental data leads to noisy 4D rotation matrices whose orthonormality must be restored.…”
Section: Introductionmentioning
confidence: 99%